The Development of Osing Kemiren Cultural Tourist Village and Community Welfare - Nurhayati, Bernadeta Resti; Koesmartadi, Christophorus; Hadinugroho, Dwi Lindarto (Jurnal Adat dan Budaya Indonesia, 2025)
Kemiren Village is located on the eastern edge of Java Island, with the Osing tribe accounting for the majority of the population. The people of Kemiren village have been very strong in passing down their ancestral customs and culture from generation to generation. Their lifestyles are closely related to agricultural life. Kemiren hamlet has been certified as a traditional tourism village due to the preservation of traditions.  This paper employed a qualitative method with an empirical approach. The primary data used was gathered through in-depth interviews with traditional leaders and members of the Kemiren village community, while secondary data was obtained from a variety of sources. The Kemiren village was designated as an Osing traditional tourism village based on the concerns of the Kemiren people, who value the traditions passed down from their ancestors in their daily lives. This tradition is carried down through marriage, inheritance, tradition, and cultural system that is still practiced today. Many ceremonies have been performed up to the present day and are nicely packaged in the form of festivals, without sacrificing the substance of the tradition itself. This cultural and traditional celebration, which involves all members of the community, brings prosperity to the people of Kemiren.